ChemInform Abstract: Bioavailability of Heavy Metals in Soils: Definitions and Practical Implementation — A Critical Review. Issue 52 (10th December 2015) - Kim, Rog‐Young; Yoon, Jeong‐Ki; Kim, Tae‐Seung; Yang, Jae E.; Owens, Gary; Kim, Kwon‐Rae
Abstract: Review: 183 refs.